The growth and yield performances of mungbean (Vigna radiata L.) as influenced by the use of cow dung and chemical fertilizers (Journal of Bangladesh Academy of Sciences, 2023)
To investigate the effect of cow dung and chemical fertilizers on the growth and yield performances of mungbean (BARI Mung 6), an experiment was carried out in the research field of the Sher-e-Bangla Agricultural University, Dhaka, during the kharif season of 2020. The experiment was laid out as a randomized complete block design (RCBD) with three replications comprising seven manure-fertilizer treatments. The results showed that the different levels of cow dung and fertilizers significantly influenced mungbean growth parameters and seed yield. The highest plant height (48.2 cm), number of leaves plant-1 (10.3), number of branches plant-1 (3.9), maximum number of pods plant-1 (19.3), seeds pod-1 (10.4), 1000-seed weight (43.4g), and the highest seed yield (1.42 t ha-1) were obtained from the application of 80% of the recommended dose of fertilizers (RDF) plus 20% cow dung. It is concluded that applying 20% cow dung (1.2 t ha-1) coupled with 80% of the recommended amount of fertilizers together produced superior results for the growth and yield of mungbean compared to applying fertilizer or cow dung alone.J. Bangladesh Acad. Sci. 47(1); 61-68: June 2023